A2A Adenosine Receptor and its Modulators: Overview on a Druggable GPCR and on Structure-Activity Relationship Analysis and Binding Requirements of Agonists and Antagonists - Cristalli, G.; Lambertucci, C.; Marucci, G.; Volpini, R.; Ben, D. (Current pharmaceutical design, 2008)
Since the discovery of the biological effects of adenosine, the development of potent and selective agonists and antagonists of adenosine receptors has been the subject of medicinal chemistry research for several decades, even if their clinical evaluation has been discontinued. Main problems include side effects due to the ubiquity of the receptors and the possibility of side effects, or to low brain penetration (in particular for the targeting of CNS diseases), short half-life of compounds, lack of effects. Furthermore, species differences in the affinity of ligands make difficult preclinical testing in animal models. Nevertheless, adenosine receptors continue to represent promising drug targets. A2A receptor has proved to be a promising pharmacological target for small synthetic ligands, and while A2A agonists are undergoing clinical trials for myocardial perfusion imaging and as anti-inflammatory agents, A2A antagonists represent an attractive field of research to discover new drugs for the treatment of neurodegenerative disorders, such as Parkinsons disease. Furthermore, the information coming from bioinformatics and molecular modeling studies for the A2A receptor has made easier the understanding of ligand-target interaction and the rational design of agonists and antagonists for this subtype. The aim of this review is to show an overview of the most significant steps and progresses in developing A2A adenosine receptor agonists and antagonists.